Uncovering the Intersections of Women’s Empowerment and Gender Equality in Climate Adaptive Capacities in Climate Hotspots for Women in Zambia - Kihoro, Esther; Lecoutere, Els; Mishra, Avni (SAGE Publications, 2024)
Climate change risks exacerbating gender inequalities in agrifood systems; hence, the importance of understanding how women’s empowerment and gender equality of climate adaptive capacities relate. Using primary gender-disaggregated intrahousehold data collected in climate hotspots in Zambia, this study shows a positive relationship between women’s empowerment in the household and intrahousehold gender equality in access, knowledge and adoption of climate-smart agricultural practices. Showing that different dimensions of women’s empowerment – gender norms, access to resources and group membership – relate differently with gender-equal adaptive capacities, the study emphasizes the importance of a contextual analysis, unpacking the prevailing key constraints to gender equality, and the need for simultaneous investments in women’s empowerment and gender-equitable access to climate information services and climate-adaptive practices.